Analisis Pengunaan Aplikasi Anates Terhadap Pengembangan Soal Assemen Formatif Siswa di MAN 1 Langkat - Wiguna, Satria (ALACRITY : Journal of Education, 2024)
The assessment questions carried out by teachers in Indonesia are only to measure knowledge thinking abilities at a low cognitive level. This is a factor in the need for MAN 1 Langkat teachers to improve the quality of assessment questions by using the Anates application.  This research aims to determine the use of the Anates application in the development of student formative assessment questions at MAN 1 Langkat. This research method uses a mixed method with the exploratory sequential design, to analyze the use of Anates's application in the development of students' formative assessment questions, a qualitative method is used, while to measure the influence between variables, a quantitative method is used. Research data was analyzed using the statistical package for the social sciences (SPSS) approach. The research results show that the use of the Anates application for MAN 1 Langkat teachers plays a very important role in improving the quality of evaluation and learning, with analysis features that enable teachers to design effective questions and support collaboration between teachers. Based on the results of hypothesis testing via the t test (partial test), it was found that the use of the Anates application had a significantly effective effect on the development of student formative assessment questions at MAN 1 Langkat, with a p value < 0.05 and tcount > ttable (4.043 > 2.01537), so the alternative hypothesis Ha is accepted.